Intensitas Lahan di Era Disrupsi Perspektif al Quran (Analisis Pemberdayaan Ekonomi Umat) - Alfian Sani (Institut Agama Islam Negeri Palopo, 2023)
Indonesia as a developing country has abundant natural resources, one of which is a large area of land. It is said, there is an area of 54 million ha of land in Indonesia that has not been touched (not yet utilized for certain purposes). The inability in terms of finance (capital) and the knowledge they have in the agricultural sector is the reason for this decline. Al-Qur'an has concepts in overcoming poverty through empowering land to become productive areas both in intensification and extensification. Through the method of thematic interpretation with a conceptual analysis approach to the pronunciation of iḥyā in the Qur'an surah An-Nahl verse 65, it intends to revive, fertilize, preserve arid land into productive areas through intensification, extensification by utilizing the latest technology. Strengthening human iḥyā processes can make maximum use of agricultural technology engineering, so as to realize sociological, conservation economics and ecological roles in order to strengthen food security for people's lives.